PENGENALAN PENGENALAN MICROSOFT OFFICE DI TK KUSUMMA MULIA SUMBERREJO BADAS KABUPATEN KEDIRI - Imam Saukani; Muhamad Rifai; Guntur Yanuar Astono; Irfin Sandra Asti; Miftakhul Huda; Hari Kurnia Safitri (Jurnal Pengabdian kepada Masyarakat, 2024)
Integrated Primary Education (TK Kusuma Mulia) is a basic education activity that is organized by, for, and with the assistance of primary education officers. Therefore, TK Kusuma Mulia is a community-driven initiative in the field of basic education, with the village head as the responsible party. A.A. Gde Muninjaya (2002:169) states: "Basic education services are a form of integrated basic education services carried out in primary education. Currently, computers are tools used to process and create work reports, whether in the form of Word, Excel, or PowerPoint data. Up until now, TK Kusuma Mulia, located in the Sumberejo Badas Pare Village, Kediri Regency, still uses conventional manual typing machines for reporting, resulting in various limitations experienced by the TK in terms of administrative operations and data management."